A two-step automated procedure based on adaptive limit and pushover analyses for the seismic assessment of masonry structures. (August 2021) - Maria D'Altri, Antonio; Lo Presti, Nicolò; Grillanda, Nicola; Castellazzi, Giovanni; de Miranda, Stefano; Milani, Gabriele
Highlights: Two-step automated procedure for the seismic assessment of masonry structures. Utilization of adaptive upper bound NURBS limit analysis and pushover with CDP in Abaqus. Procedure working under in-plane and combined in- and out-of-plane loading conditions. Cohesive-frictional contact-based interfaces are used in step2 with masonry crushing allowed. The effectiveness of the procedure is shown on a 3D full-scale masonry building. Abstract: In this paper, a two-step automated procedure based on adaptive limit and pushover analyses is developed for the seismic assessment of masonry structures. Inspired by an akin procedure previously developed by the authors for the out-of-plane behaviour, the procedure herein presented is extended to in-plane and combined in- and out-of-plane loading conditions, accounting also for the effect of masonry crushing failure. In the first step, an upper-bound adaptive limit analysis tool is used to predict the collapse mechanism (and the corresponding multiplier) of the structure given a certain loading condition. A novel ad-hoc routine is then developed and utilized for the automatic import of the collapse mechanism geometry of any complexity into a solid model ready to be used in a finite element framework. In the second step, cohesive-frictional contact-based interfaces are automatically inserted in the cracks of the collapse mechanism formerly obtained, and a pushover analysis is conducted to investigate the load–displacement response of the structure. A series of parametric analyses are conducted to highlight the effect of different mechanical assumptions. Finally, the effectiveness of the procedure proposed is shown on a full-scale masonry building case study.